2021
DOI: 10.1088/1742-6596/2054/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Modern concepts and application of soft robotics in 4D printing

Abstract: Recent developments in (AM) additive developed normally Three-dimensional (3D) printing is a term used to describe printing that is three-dimensional in nature, have enabled researchers to use traditional production methods to create previously unthinkable, complex shapes. Usage of smart materials by the way of adopting the external stimuli in printing is part of a 3D-printing research division called 4D-printing.4D-printing allows for the development of dynamically controllable shapes on-demand by the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The integration of 3D printing and SRPs can help to develop soft robotics of a variety of sizes for performing complex functions with minimal manipulation. [ 530–533 ] Recent studies showed the development of smart grippers, actuators, and robots for different applications. [ 534–540 ] For instance, Cecchini et al [ 381 ] exploited the reshaping ability of humidity‐responsive materials to develop a seed‐like soft robot by using FDM printing, as illustrated in Figure A.…”
Section: Applications Of Additively Manufactured Srpsmentioning
confidence: 99%
“…The integration of 3D printing and SRPs can help to develop soft robotics of a variety of sizes for performing complex functions with minimal manipulation. [ 530–533 ] Recent studies showed the development of smart grippers, actuators, and robots for different applications. [ 534–540 ] For instance, Cecchini et al [ 381 ] exploited the reshaping ability of humidity‐responsive materials to develop a seed‐like soft robot by using FDM printing, as illustrated in Figure A.…”
Section: Applications Of Additively Manufactured Srpsmentioning
confidence: 99%
“…PolyJet printing technique uses direct jetting of photopolymer ink droplets and subsequently solidified onto a build platform [103]. This technique is extensively applied to fabricate smart materials [104]. To date, 4D-printed structures developed by using polyjet printing are actuated through heat [105].…”
Section: D Printing Technologiesmentioning
confidence: 99%